PEMBERDAYAAN EKONOMI MASYARAKAT PESISIR DI JAWA TENGAH - Wiwin Widiastuti; Alfina Handayani (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2014)
The research purposes are to analyze the performance of Coastal Community Economic Empowerment Program and to analyze the strategy of coastal community economic empowerment that appropriate to the need of coastal community. The research locus are Batang Regency and Pati Regency. Batang regency is the location of Coastal Community Economic Empowerment Program Implementation namely Coastal Women Empowerment Program, while Pati regency as the location of Salt Farmers Empowerment. The research result show that the performance of Coastal Economic Empowerment Program in Central Java Province were assessed as good and appropriate to the need of coastal community, although part of the program were assessed not really appropriate to the need of coastal community. Only few of local government had budget allocation for coastal community economic empowerment assistance program. The foward strategy of coastal community economic empowerment program are to dig the community’s real need, to socialize that it’s need of community awareness to be empower, to do training, to facilitate market acces and bussiness facilities, and to assist the empowerment program by local government.